ANALISIS KINERJA TATA USAHA DALAM PELAKSANAAN ADMINISTRASI KESISWAAN DI SMK SWASTA TARUNA BANGSA SAWIT SEBERANG TAHUN PELAJARAN 2024-2025 - Arvian Frananta; Hamidah Darma; Mardiati Mardiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the administrative performance in implementing student administration at Taruna Bangsa Sawit Seberang Private Vocational School. The method used in this study is descriptive qualitative. Data were collected through observation, interviews, and documentation. The results indicate that the administrative performance in managing student administration has been running well and can meet the school's needs. However, the obstacles faced by administrative staff include: 1) limited human resources in the administrative department; 2) faulty equipment such as computer errors, broken printers, and lost data, which hinder work; 3) inadequate facilities and infrastructure; and 4) high workloads that cause delays in completing tasks. Overall, this study concludes that good performance can support smooth school administration. To achieve this goal, school needs, especially in the administrative department, must be improved to ensure effective and efficient administrative processes.